Cubic liquid crystalline nanoparticles containing a polysaccharide from Ulva fasciata with potent antihyperlipidaemic activity - Azza A. Matloub; Mona M. AbouSamra; Alaa H. Salama; Maha Z. Rizk; Hanan F. Aly; Ghada Ibrahim Fouad (Elsevier, 2018)
The present study involves the preparation of cubic liquid crystalline nanoparticles (cubsomes) for liver targeting to assess the potential of a formulated bioactive polysaccharide isolated from the hot aqueous extract of Ulva fasciata as an alternative natural agent with anti-hyperlipidaemic activity. Cubosomal nanoparticles were prepared by disrupting the cubic gel phase of the polysaccharide and water in the presence of a surfactant. Different lipid matrices and stabilizers were tested. All the formulations were in the nanosize range and showed sufficient negative charge to inhibit the aggregation of the cubosomes. Drug entrapment efficiencies (EEs%) were determined and in vitro release studies were performed. Transmission electron microscopy (TEM) and differential scanning calorimetry were used to analyze the loaded cubosomal nanoparticles containing glyceryl monostearate (GMO 2.25 g), poloxamer 407 (0.25 g) and 50 mg of the polysaccharide. A preclinical study comparing the cubic liquid crystalline nanoparticles containing polysaccharide to fluvastatin as a reference drug in hyperlipidaemic rats was conducted. The rats treated with the polysaccharide- loaded cubosomes showed significant decreases in total cholesterol (TC), triglycerides (TG) and total lipid (TL) compared to the untreated HL rats. In addition, oxidative stress and antioxidant biomarkers were measured in the HL rats. Compared to the untreated HL rats, the cubosome treated rats showed a significant reduction in malondialdehyde (MDA), whereas insignificant changes were detected in nitric oxide (NO), glutathione (GSH) levels and total antioxidant capacity (TAC). Further, vascular and intercellular adhesion molecules (VCAM, ICAM), and myeloperoxidase were demonstrated. A histopathological examination was conducted to study the alterations in histopathological lesions and to document the biochemical results. In conclusion, this study demonstrates the superiority of using a natural lipid regulator such as polysaccharide loaded cubosomes instead of fluvastatin.